Perspectives in control engineering : technologies, applications, and new directions - Samad, Tariq; John Wiley & Sons; IEEE Xplore (Online service) (New York : IEEE Press, 2001)
"What important research developments are under way in control science and engineering? What are key challenges in control technology applications to different domains? What new directions are being charted for control systems? Now practicing control engineers and students can find accessible answers to these multifaceted control issues without the intensive mathematical analysis usually found in control systems books. This all-in-one resource brings you state-of-the-art research results by contributors who are leading experts in control. You will find insightful introductions and discussions of future trends for a range of control technologies and applications, including: * Computer-aided control system design * Discrete event systems * Intelligent control * Industrial process control * Intelligent transportation systems. PERSPECTIVES IN CONTROL ENGINEERING is the one-stop volume you need to gain an overview of the latest advances in control systems." Sponsored by: IEEE Control Systems Society.
Introduction. Acknowledgments. CONTROL TECNOLOGIES. Real-Time Computing and Control (Scott Bortoff). Discrete-Event Systems and Their Optimization (Edwin K. P. Chong). Computer-Automated Control System Design (Georg Grubel). System Modeling (Pradeep Misra). Intelligent Control: An Overview of Techniques (Kevin M. Passino). Neural, Fuzzy, and Approximation-Based Control (Jay A. Farrell and Marios M. Polycarpou). Supervisory Hybrid Control Systems (Michael D. Lemmon). Variable Structure and Sliding-Mode Control (Fumio Hamano and Youchan Kim). Control Systems For "Complexity Management" (Tariq Samad). CONTROL APPLICATIONS. Control of Multivehicle Aerospace Systems (Jorge Tierno, Joseph Jackson, and Steven Green). Affordable Flight Control for Aircraft and Missiles (Kevin A. Wise). Industrial Process Control (Michael A. Johnson and Michael J. Grimble). Power System Control and Estimation in A Competitive Environment (Christopher L. DeMarco). Intelligent Transportation Systems: Roadway Applications (Umit Ozguner). Automotive Powertrain Controller Development Using CACSD (K. Butts, J. Cook, C. Davey, J. Freidman, P. Menter, S. Raman, N. Sivashankar, P. Smith, and S. Toeppa). Building Control and Automation Systems (Albert T. P. So). Controlling Civil Infrastructures (B. F. Spencer Jr. and Michael K. Sain). Robot Control (Bruno Siciliano). Control of Communication Networks (R. Srikant). Index. About The Editor.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Automatic control; Control theory; Electronic books